Detection of Bacillus Cereus Using Bioluminescence Assay with Cell Wall-binding Domain Conjugated Magnetic Nanoparticles - Park, Chanyong; Kong, Minsuk; Lee, Ju-Hoon; Ryu, Sangryeol; Park, Sungsu (Biochip journal, 2018)
Bacillus cereus can cause blood infections (i.e., sepsis). Its early detection is very important for treating patients. However, an antibody with high binding affinity to B. cereus is not currently available. Bacteriophage cell wall-binding domain (CBD) has strong and specific binding affinity to B. cereus . Here, we report the improvement in the sensitivity of an ATP bioluminescence assay for B. cereus detection using CBD-conjugated magnetic nanoparticles (CBDMNPs). The assay was able to detect as few as 10 colony forming units (CFU) per mL and 10 3 CFU per mL in buffer and blood. CBD-MNPs did not show any cross-reactivity with other microorganisms. These results demonstrate the feasibility of the ATP assay for the detection of B. cereus .